The Relationship Between Transformational Leadership, Work Motivation, School Culture, and Work Ethic with the Performance - Abid Rahman; Ni Luh Gede Erni Sulindawati; Basilius Redan Werang (Journal of Education Reseach and Evaluation, 2026)
The low level of teacher performance in one school indicates the need to identify determinant factors influencing such performance. The suboptimal roles of leadership, work motivation, school culture, and work ethic are presumed to contribute to variations in teachers’ performance outcomes. This study aims to comprehensively analyze, evaluate, and examine the relationships and contributions of transformational leadership, work motivation, school culture, and work ethic to teacher performance.This research employed a quantitative approach using an ex-post facto method with a correlational design. The population consisted of 258 teachers, with a sample of 157 teachers selected through proportional random sampling. A total of 151 completed questionnaires were returned and analyzed. Data were collected using a closed-ended Likert-scale questionnaire that had been tested for validity and reliability. Data analysis procedures included assumption testing, Spearman correlation analysis, and ordinal regression. The findings indicate that transformational leadership and work ethic have a positive and statistically significant relationship with teacher performance, with work ethic emerging as the most dominant variable. In contrast, work motivation and school culture were not statistically significant predictors in the regression model. Simultaneously, the four variables collectively contributed significantly to teacher performance. The study concludes that strengthening work ethic and transformational leadership constitutes the primary strategy for improving teacher performance. Practically, professional development initiatives should prioritize the cultivation of teachers’ work character and the enhancement of principals’ leadership quality.